Efficient removal of non-steroidal anti-inflammatory ibuprofen by polypyrrole-functionalized magnetic zeolite from aqueous solution: kinetic, equilibrium, and thermodynamic studies. Issue 3 (11th February 2023) - Negarestani, Mehrdad; Mollahosseini, Afsaneh; Farimaniraad, Hamidreza; Ghiasinejad, Hossein; Shayesteh, Hadi; Kheradmand, Asiyeh
ABSTRACT: This study investigated the adsorption performance of ibuprofen onto magnetic zeolite clinoptilolite modified with polypyrrole (Clino/Fe3 O4 /Ppy). The synthesized nanocomposite was characterized by scanning electron microscope, Fourier-transform infrared spectroscopy, Energy-dispersive X-ray analysis, Brunauer-Emmett-Teller, and X-ray powder diffraction analysis. The obtained results demonstrated that the high surface area of zeolite could significantly impact the adsorption process. Various parameters were studied to determine the optimum condition, including contact time, pH, adsorbent dosage, initial ibuprofen concentration, temperature, and mixing speed. The optimization of contact time revealed a high performance in the first 5 min of the adsorption process. Furthermore, when the temperature rose, the efficiency increased as well, with the highest efficiency being achieved at 45°C. Some isotherm models and kinetics equations were used to analyze equilibrium data. The kinetic study revealed that the adsorption process followed pseudo-second-order (R 2 = 0.9972), and the isotherm investigations showed that Langmuir (R 2 = 0.9941) was an appropriate model for explaining the equilibrium of the adsorption process. Based on the obtained thermodynamic factors, it was represented that the adsorption process was endothermic and spontaneous. Based on the research findings, Clino/Fe3 O4 /PPy nano-adsorbent developed in this study might be a helpful strategy for removing ibuprofen from various water sources. GRAPHICAL ABSTRACT: uf0001